6 - She is so Pretty, Look at her Hair’: Perspectives on the Racialisation of Mixed- Race Persons in Ghana - Yaa Oduro, Georgina; Geoffrion, Karine; Prah, Mansah (Africa Development, 2024)
This article interrogates the processes of the racialisation of hair and skin colour of ‘mixed-race’ Ghanaians in the specific context of Ghana. The article draws on the findings of a larger qualitative multisite study that explored the lived experiences and identity construction of Ghanaian mixed-race persons living in Ghana and Canada, Informed by race and racialisation theories, the article argues that hair politics cannot be discussed without considering how skin colour and gender also contribute to shaping the racial categorisation of mixed-race individuals in Ghana. The authors show how Ghanaian society ‘others’ and racialises mixed-race Ghanaians (for example, through school regulations on hair and hair style); how mixed-race individuals navigate the racial gaze, discourses and practices around their body; how they reproduce and challenge racialised considerations and imaginaries; and how they perform their own racial identities through their hair. The article links these narratives with the ideals of white racial hegemony that permeate society. Acknowledging mixed-race Ghanaians’ experiences of privilege, the authors argue that the valuation of their whiteness by the majority population is not straightforward and does not lead mixed-race individuals to self-identify as whites. Mixed-race Ghanaians, rather, have fluid experiences i terms of privileges and discrimination based on context and interactions.